Hierarchical chirality expression of gemini surfactant aggregates via equilibrium between chiral nucleotide and nonchiral mono‐anions. Issue 7 (28th April 2020) - Dedovets, Dmytro; Martin, Barbara; Okazaki, Yutaka; Buffeteau, Thierry; Pouget, Emilie; Oda, Reiko
Abstract: The assembling behaviors of nonchiral dicationic amphiphilic molecules (gemini) in the presence of the mixture of chiral anionic nucleotides and nonchiral anions are investigated. We demonstrate that subtle balance of various physico‐chemical parameters and the competition between chiral and nonchiral anions at the interface of gemini assemblies influences the expression of molecular chirality at the micrometer scale through the hierarchical molecular assembly. Abstract : Subtle balance between chiral nucleotides and nonchiral counterions required for hierarchical chirality expression from nucleo‐gemini assemblies.